2005
DOI: 10.1128/mcb.25.6.2364-2383.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Hematopoietic Progenitor Kinase 1 Involves Relocation, Autophosphorylation, and Transphosphorylation by Protein Kinase D1

Abstract: Innate and adaptive immune functions are governed by instructive signals from receptors that sense pathogens and toxins. Ligation of lymphocyte antigen receptors triggers a series of characteristic events that is initiated by activation of Src family tyrosine kinases followed by recruitment and activation of Syk and BTK family nonreceptor tyrosine kinases (18). The ensuing tyrosine phosphorylation provides docking sites for SH2 and PTB domains on adaptor proteins and enzymes, which assemble into a spatially hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
70
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 44 publications
4
70
0
Order By: Relevance
“…In addition, previous study also found that HPK1 autophosphorylation occurs predominantly on threonine residues (10). Using PhosphoSitePlus program, we identified two threonine residues, Thr-349 and Thr-355, in HPK1-PR region (Fig.…”
Section: Hpk1 Interacts With Skp1 Rbx1 and Cul7 But Not Cul1-mentioning
confidence: 99%
“…In addition, previous study also found that HPK1 autophosphorylation occurs predominantly on threonine residues (10). Using PhosphoSitePlus program, we identified two threonine residues, Thr-349 and Thr-355, in HPK1-PR region (Fig.…”
Section: Hpk1 Interacts With Skp1 Rbx1 and Cul7 But Not Cul1-mentioning
confidence: 99%
“…More recent reports advance the concept that PKD activity modulates JNK signaling to c-jun at multiple levels. Thus, PKD activates distinct MAP3Ks operating in JNK activation pathways, including hematopoietic progenitor kinase, HPK1 [10] and, when activated in response to oxidative stress [11], the apoptosis signaling kinase ASK1 [12]. In our own previous studies we found that purified PKD directly phosphorylated a GST-c-jun(1-89) (N-terminal) fusion protein in vitro, but the sites were not identified [13].…”
mentioning
confidence: 95%
“…9,10 HPK1 activation involves binding of cell-specific adaptor proteins, relocation to the plasma membrane, autophosphorylation and transphosphorylation by protein kinase D1. [11][12][13] While a role for HPK1 in the regulation of T-cell apoptosis was already suggested, 14 our recent studies have shown proteolytic processing of HPK1 into HPK1-C in non-apoptotic preactivated primary T cells. 15 In this study, the cleavage product HPK1-C sensitizes towards T-cell receptor-mediated cell death, while full-length HPK1 enables activation and survival of T cells.…”
mentioning
confidence: 99%